PELATIHAN PENGGUNAAN PLATFORM GAMIFIKASI EDUKATIF GUNA PENGUATAN PENDIDIKAN DI ERA PANDEMI COVID 19 BAGI GURU SEKOLAH DASAR DAN MENENGAH DI KOTA DEPOK - Yuyun Khairunisa; Yeni Nurhasanah; Sari Setyaning Tyas; Septia Ardiani; Handika Dany Rahmayanti (Universitas Mataram, 2022)
The use of distance learning technology (e-learning) needs to be addressed so that learning objectives can be achieved effectively even though the activities are not carried out face-to-face in the classroom. One way to increase the focus and interest of students in learning activities is the use of elements in games in e-learning learning media or also known as gamification. Most of the gamification platforms are licensed or paid, so Teachers have to pay extra. The solution to this problem is to provide teachers with training and mentoring on the use of the online gamification platform where the application is free and simple to use. The purpose of this community service activity is to introduce and improve the digital competence of teachers and educators in using online gamification platforms (on the network) as a learning medium. The method used in service activities is the method of training and mentoring. The results of this community service activity are in the form of stages of making learning media using the wordwall.net gamification platform, namely opening the wordwall.net page, selecting Sign Up, setting up myActivities display, making Maze Chase, and evaluating/viewing student work. The conclusion of this activity is the increase in the digital skills of the activity participants, game and quiz-based learning media products, as well as practical guidebooks for using the gamification platform. The material presented is useful for teachers and educators in preparing digital teaching materials based on games and quizzes.